Impact of breast cancer genetic testing in Brazilian patients: insights from the MAGENTA study - Scarelli, Evelin; Teixeira, Carolina Meyn; Viana e Silva, Nathália; Bredariol, Andrea Silveira dos Santos; Baracho, Giovana Sivieri; Souza, Fabiano Hahn; Holtz, Luciana (Frontiers in Oncology, 2026)
IntroductionBreast cancer is the most prevalent cancer among women in Brazil, with up to 10% of cases linked to hereditary factors. Genetic testing and counseling are critical for identifying hereditary breast cancer risk, guiding treatment decisions, and preventing cancer in high-risk populations.ObjectivesThis study aimed to analyze the experience, perspectives, and access barriers to breast cancer genetic testing in the Brazilian respondents of the Multinational Survey Study Assessing GENetic Testing and Counseling Among Patients with Breast Cancer (MAGENTA) study.MethodsA 38-multiple-choice question, branched survey was distributed by patient advocacy agencies to collect sociodemographic and patient-perspective data about their experience with breast cancer genetic testing. A multivariate analysis was conducted to explore the association between sociodemographic variables and the genetic testing status.Results207 breast cancer patients completed the survey. In this cohort, the rates of genetic testing and counseling were 81.6% and 60.4%, respectively. 66.7% of respondents reported a high or advanced educational level. Notably, 71.7% of patients reported that genetic testing changed their treatment plans, and 77.1% of those who took the test were willing to test their familiars. In addition, 98.7% stated they did not regret undergoing genetic testing. Higher income was independently associated with higher odds of undergoing genetic testing (OR: 4.43 [95% CI: 1.64;13.11]; p = 0.0011), while having more than 50 years-old was associated with a lower odds of undergoing testing (OR: 0.21 [95% CI: 0.08;0.56]; p=0.0018). Barriers such as costs and limited awareness were prominent, with 89% of patients in Brazil reporting low awareness of genetic testing prior to their diagnosis.ConclusionsThe survey respondents in Brazil comprised a highly educated and financially secure group of patients. Although not generalizable to the entire Brazilian population, our results revealed that even in a highly educated and well-informed cohort there is a strong association between age and income level with genetic testing. These findings expose the real-world challenges for increasing genetic testing coverage in Brazil, where testing is only warranted in the private health system, highlighting the need for health policies to increase test availability for lower income brackets.